Hierarchy-inductive modeling for identification of compromise between price of accommodation and level of its fire safety - Myroshnyk, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Technology for decision making process while accommodation buying, based on analysis of the compromise between its cost and fire safety level, has been offered. The algorithms of hierarchy-inductive modeling, with the help of which identification of price and fire safety level functions is realized has been proposed.